What do we know about Africa? - Brown, Barbara B.; Weinstein, Tanya; Boston University ([Boston, Mass.] : Boston University : Insight Media [distributor], 1995)
Discusses commonly held western stereotypes about Africa and then presents accurate information on African culture and geography
Based on the original program created by Leslie Belay, Priscilla Hinkley, and Aida Levi. Revised by Barbara B. Brown and Tanya Weinstein
Title from title screen
Copy available in DVD format
Music, David Hewitt
Keywords: Africa; Africa -- History; Africa -- Study and teaching; Africa -- Social conditions